Direct‐Write Printed, Solid‐Core Solenoid Inductors with Commercially Relevant Inductances. Issue 1 (21st October 2018) - Gu, Yuan; Park, Donghun; Bowen, David; Das, Siddhartha; Hines, Daniel R.
Abstract: Additive manufacturing has the potential to fabricate passive components (e.g., capacitors, resistors, inductors, etc.) of a radio frequency (RF) circuit with minimized dimensions and controllable shapes in order to realize high‐density RF electronics for applications such as high resolution radars, healthcare monitors, and wearable sensors that involve high data‐rate transmissions. Here a novel procedure to direct‐write 3D, solid‐core solenoid‐inductors with polymer‐core, iron‐core, and ferrite‐core using aerosol‐jet 3D printing is reported. Solid‐core solenoid inductors that are of order 30 mm 3 in size are achieved and most importantly, commercially relevant inductance values of microhenry (for polymer‐core) to tens and hundreds of millihenry (for ferrite and iron cores) are demonstrated, which has been beyond the scope of the previous attempts in fabricating additively manufactured inductors. Furthermore, the authors direct‐write printed inductors of various geometries and pinpoint the geometry‐dependent inductor performances. Abstract : A methodology for the application of additive manufacturing, using aerosol‐jet (AJ) 3D printing, for the fabrication of solenoid type inductor structures is developed. 3D printed inductors are demonstrated where high magnetic permeability materials are integrated into the core accomplishing commercially relevant inductance values.